Notes on Hampala (Cyprininae) Distribution from Six Localities in Sabah - Jeffrine Japning, Rovie-Ryan; Kelvin Pudun, Dennis; Yuzine, Esa; Khairul Adha, A.Rahim; Zaidi, Ibrahim; Zulkifli, Ahmad; Edward, Marilyn-Jaoi (Department of Wildlife and National Parks, 2008)
This study was conducted from the 9th until 16th November 2003. A total of 31 fish from six localities throughout Sabah were sampled. It was found that at least four forms of Hampala inhibit the Sabah river system. The widely spread form, H. macrolepidota and the Bornean endemic form, H. bimaculata was recorded on the west coast region of Sabah. The Sabah endemic form, H. sabana dominated the central eastern region of Sabah. The south eastern region demonstrates the existence of two forms distinctly different by their number of gill rakers: (I) Tawau population (gill raker counts: 10-11) and Kalabakan population (gill raker counts: 12-13). The Kalabakan form could possibly be a crytic species.